Rest Time Analysis Based on Operator's Workload Using a Physiological Measures at PT. Amanah Insanillahia - Maria Isfus Senjawati; Khairun Nadiyah; Diego Arya Permana (Journal of Industrial Engineering and Halal Industries)
Amanah Insanillahia is a manufacturing company that produces bottled drinking water (AMDK). The high demand for drinking water production at PT Amanah Insanillahia requires workers to do their work as much as possible in order to achieve the targets desired by the company. In addition to the targets to be achieved, the company must also pay attention to the operator's workload. Workload related to physical fatigue will reduce performance and increase errors at work. This study aims to determine the operator's rest time using a physiological approach. The method used is quantitative with data collection carried out directly. The object of research is the population of employees in the 220 ml packaging station. Heart rate measurement is done by utilizing the 10-beat method. The results show that the value of K < S, the energy expended during work is less than the standard value of energy expended (men = 5 kcal/min, women = 4 kcal/min), then Rt = 0. This means that the rest time provided by the company is adequate, so there is no need for additional resting time at the 220 ml packaging station.